Water-Stable High Lithium-Ion Conducting Solid Electrolyte of Li1.4Al0.4Ge0.2Ti1.4(PO4)3–LiCl for Aqueous Lithium-Air Batteries - Bai, Fan; Kakimoto, Kouichi; Shang, Xuefu; Mori, Daisuke; Taminato, Sou; Matsumoto, Mitsuhiro; Takeda, Yasuo; Yamamoto, Osamu; Izumi, Hiroaki; Minami, Hironari; Imanishi, Nobuyuki (Frontiers in Energy Research, 2020)
Aqueous lithium-air batteries are one of the most promising batteries for electric vehicles because of its high energy and power density. The battery system consists of a lithium anode and an aqueous solution catholyte, which are separated by a water-stable lithium-ion-conducting solid electrolyte, and an air electrode. The theoretical energy density of this system is 1,910 W h kg–1, which is around five times higher than that of conventional lithium-ion batteries. A key component of this system is the water-stable lithium-ion-conducting solid electrolyte. In this work, we have developed a water-stable and water-impermeable solid electrolyte with a high lithium-ion conductivity of around 10–3 S cm–1 at room temperature by the addition of epoxy resin and LiCl into a tape-cast NASICON-type Li1.4Al0.4Ge0.2Ti1.4(PO4)3 film. The aqueous lithium-air battery with the solid electrolyte separator was successfully cycled at 0.5 mA cm–2 and 25°C in an air atmosphere.